Factors Affecting Bird Diversity in the Wetlands of Muara Gembong, Indonesia - Fathani, Muhammad Hamas; Mulyani, Yeni Aryati; Mardiastuti, Ani; Djatmiko, Wibowo Agung (Jurnal Manajemen Hutan Tropika, 2025)
Marshlands and backswamps are among the threatened habitats in Indonesia, along with mangroves, particularly in Java due to area development and land conversion. Muara Gembong is one of the remaining wetlands in Java and serves as one of the last refuges for the bird community in wetlands, particularly mangrove and marsh-associated birds. We observed bird communities and collected eleven habitat variables in three habitats, namely mangrove, marsh, and fishpond, to see which variable affects bird abundance and diversity most. We found out that the total number of plant species, along with the number of tree, understory, and shrub species, were the strongest factors affecting bird diversity in Muara Gembong. Separate analysis in each habitat, however, reveals that different abiotic factors also strongly correlate with bird diversity. Vegetation correlates strongly with bird diversity in mangroves and marshes, while pH and turbidity play a strong role in bird diversity in fishponds.